La vida de Lazarillo de Tormes y de sus fortunas y adversidades - Otal Piedrafita, Ma. Teresa (María Teresa) (Castalia prima ;, 2012)
Presents the text of the classic novel in which young rogue Lázaro recounts his adventures and describes how he outwits his series of masters, with modernized spelling, an explanatory introduction, notes, and activities.